INGLIS HÁM QARAQALPAQ TILLERINDE ELIKLEWISHLERDIŃ SALÍSTÍRMALÍ ÚYRENILIWI - Bayımbetova, M.B. (SCIENCE and SOCIETY, 2024)
This article studies imitative words in the English and Karakalpak language, their origin and phenomenon. Both of these languages have imitative words and they have unique peculiarities at the same time. In this work, study and analysis of specific features and classification of imitation words in English and Karakalpak languages.